Застосування процеса флюїдизації для заморожування ягід - Паламарчук, Ігор Павлович; Кюрчев, Сергій Володимирович; Верхоланцева, Валентина Олександрівна; Паляничка, Надія Олександрівна; Palamarchuk, I.; Kiurchev, Serhii; Verkholantseva, Valentyna; Palianychka, Nadiia (Мелітополь : 2022, 2022)
UA: Заморожування є способом консервування найкращим чином зберігає структуру, властивості- та харчову цінність продуктів харчування. До того ж консервування харчових продуктів заморожуванням має низьку, в порівнянні з іншими способами консервування, енергоємністю. Поєднання вібраційної та поточної технологій при реалізації семіфлюідизації у конвеєрних вібромашинах обумовлює реалізацію автоматизації виробничого процесу, гармонійне співвідношення його основних структурних складових, здійснення ефективної об’ємної дії на продукцію, що відповідає вищим формам досконалості технологічного обладнання. Розвиток вібраційних конвеєрних машин веде початок із хвильових та вібраційних конвеєрів. Інтенсивна тепломасообмінна дія у досліджуваному семіфлєідизаційному процесі на поверхневий шар сировини створює водночас проблеми його переохолодження та нерівномірності пошарової обробки. Тому є перспективним при транспортуванні продукції в зоні обробки використовувати віброконвеєрні та хвильові технології, що дозволяють створити сприятливі умови для контактної взаємодії окремих ягід та холодоносія; реалізувати технологічний рух у безперервному режимі; зменшити та усунути взагалі використання непродуктивної праці при здійсненні допоміжних операцій; створити загальне керування динамічним станом системи, в якій відбувається технологічна дія; мінімізувати механічні пошкодження ягідної продукції. EN: Freezing is a way of canning that best preserves the structure, properties and nutritional value of food. In addition, canning food by freezing has a low, compared to other methods of canning, energy consumption. The combination of vibration and current technologies in the implementation of semifluidization in conveyor vibrating machines determines the implementation of automation of the production process, the harmonious ratio of its main structural components, the implementation of effective volume action on products that meet the highest forms of technological equipment. The development of vibrating conveyor machines begins with wave and vibrating conveyors. Intensive heat and mass transfer action in the studied semifleidization process on the surface layer of raw materials creates both problems of its supercooling and uneven layer-by-layer processing. Therefore, it is promising to use vibroconveyor and wave technologies when transporting products in the processing area, which allows to create favorable conditions for contact interaction of individual berries and coolant; to implement technological movement in a continuous mode; reduce and eliminate the use of unproductive labor in the implementation of ancillary operations; create general management of the dynamic state of the system in which the technological action takes place; minimize mechanical damage to berry products. Frozen berries have a number of undeniable ad-vantages: they do not require additional preparation costs, are almost ready to eat, and most importantly, thanks to modern technologies, they retain almost twice as much nutrients as with other canning methods. Increasingly, there are risks associated with internal and external factors, as well as problems with excess yields that threaten not to sell the product fresh. short shelf life immediately after harvest, which increases the critical dependence on market prices. The use of such freezing gives, first of all, a low degree of product damage, minimally reduces the biological value and taste characteristics, and the use of freezing does not significantly affect the quality of the thawed product.
Application of fluidization process for berry freezing
Паламарчук І. П., Кюрчев С. В., Верхоланцева В. О., Паляничка Н. О. Застосування процеса флюїдизації для заморожування ягід. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 2. C. 135-142.
Keywords: процес; обладнання; флюїдизація; продукція; ягода; process; equipment; fluidization; products; berry